1980
DOI: 10.1159/000207213
|View full text |Cite
|
Sign up to set email alerts
|

Micromegakaryocytes in Human Bone Marrow

Abstract: Micromegakaryocytes (MMK) were defined morphologically by the cell area, nucleus form and cytoplasmic structure. Bone marrow smears of 7,156 patients were retrospectively analyzed. MMK were found most frequently and abundantly in acute non-lymphatic leukaemia, chronic myeloid leukaemia and pre-leukaemia. The presence of more than 10% MMK in the megakaryocyte population suggests a pre-leukaemic condition or non-lymphatic leukaemia. The platelet production of MMK is probably quantitatively normal although a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 6 publications
1
4
1
Order By: Relevance
“…Promyelocytes are estimated to be 15–20 μm in diameter . By this criterion, small numbers of micromegakaryocytes were present in smears without anticoagulant in most of our subjects, which is in agreement with previous observations that small numbers of micromegakaryocytes may be found in BM smears of some patients without hematological diseases and in apparently healthy individuals .…”
Section: Discussionsupporting
confidence: 92%
“…Promyelocytes are estimated to be 15–20 μm in diameter . By this criterion, small numbers of micromegakaryocytes were present in smears without anticoagulant in most of our subjects, which is in agreement with previous observations that small numbers of micromegakaryocytes may be found in BM smears of some patients without hematological diseases and in apparently healthy individuals .…”
Section: Discussionsupporting
confidence: 92%
“…Though the morphological abnormalities of megakaryocytes have been reported in AML (19), preleukaemia (7, 20, 21) and in myeloproliferative disorders (22, 23), our study demonstrated a higher frequency of abnormal megakaryocytes in patients with AML and MDS than was observed previously.…”
Section: Discussioncontrasting
confidence: 75%
“…Micromegakaryocytes, fully mature MK with low ploidy, are usually seen in leukaemic and preleukemic bone marrow 36 . However, Muhury et al 37 report the presence of micromegakaryocytes in 42% of patients with immune thrombocytopenia and propose it as a marker of disturbed MK ploidization and maturation.…”
Section: Discussionmentioning
confidence: 99%